(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aims to address a very important topic, which is the phenomenon of school violence prevalent within educational institutions, and seeks to control this behaviour within its social context by linking it to factors outside the educational institution surrounding the student. This is done by investigating how this phenomenon is related to the most important social institution, which is the family, and by exposing the family factors that contribute to the spread of violent behaviour among students.